2014
DOI: 10.1021/jp503184d
|View full text |Cite
|
Sign up to set email alerts
|

The Response of a 3He Fermi Liquid Droplet to Vibronic Excitation of an Embedded Glyoxal Molecule

Abstract: The zero-phonon line (ZPL) and the sideband in the vibronic spectrum of a single glyoxal molecule inside a (3)He droplet are analyzed within the framework of the Lax formalism. The new theory takes full account of the coupling of the molecule to the single particle-hole (PH) and collective excitations of the doped Fermionic droplet. The effect on the coupling of the wavevector dependence of the effective (3)He mass and the large local density of the first (3)He shell, resulting from the interaction with the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 34 publications
0
11
1
Order By: Relevance
“…Fermi excitations have been observed in the absorption spectrum of doped helium-3 droplets, as shown experimentally in [1] and interpreted theoretically in [1,6,7]. It was found that Fermi excitations essentially affect the spectrum in the vicinity of the zero-phonon line (ZPL) by causing: (i) the disappearance of the dip (existing for helium-4 droplets) between the zero-phonon line and the phonon tail; (ii) a 0.5 cm À1 broadening and strong asymmetry of the line.…”
Section: Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…Fermi excitations have been observed in the absorption spectrum of doped helium-3 droplets, as shown experimentally in [1] and interpreted theoretically in [1,6,7]. It was found that Fermi excitations essentially affect the spectrum in the vicinity of the zero-phonon line (ZPL) by causing: (i) the disappearance of the dip (existing for helium-4 droplets) between the zero-phonon line and the phonon tail; (ii) a 0.5 cm À1 broadening and strong asymmetry of the line.…”
Section: Introductionmentioning
confidence: 58%
“…Such dependence can then be derived from their orthogonality conditions [12]. The procedure has been illustrated in two previous papers [1,7]. A salient point is that the dependence of the matrix elements on the radial momentum transfer q can be conveniently transformed into an approximate dependence on the energy transfer E. The approximation is actually the matching at the cross-over energy E co ¼ 2m k 2 F =ðm F Ã Þ 2 between the low-energy limit, where Q ( k F , and the high-energy limit, where Q ffi ð2mEÞ 1=2 and Q ) k F , with k F the Fermi wave vector and m F ⁄ the 3 He atom effective mass [7].…”
Section: Contribution Of the Fermi Seamentioning
confidence: 99%
See 3 more Smart Citations